PERANCANGAN SISTEM INFORMASI LITERASI MENGGUNAKAN METODE R&D DI SMK GEMA PELITA - Dani Pradana Kartaputra; Dedy Apriady; Sulastri (Jurnal Teknologi Informasi dan Komunikasi, 2023)
Students' interest in reading at various levels of education has continued to decline in recent years. This decline in reading interest can have a negative impact on students' academic abilities and personal development. Therefore, increasing students' interest in reading is a major challenge in the world of education. To face this challenge, researchers developed a Literacy Information System Using the R&D Method at Gema Pelita Vocational School which aims to increase students' interest in reading through innovative technology-based approaches. The Literacy Information System that was built provides access to various reading materials according to students' reading interests. Apart from that, there is also a literacy event feature which aims to develop students' writing literacy skills. This Literacy Information System also provides a recapitulation of student reading, graphs of student reading literacy progress, and literacy progress statistics to see the literacy progress of each student. With this Literacy Information System, it is hoped that students will be able to increase their interest in reading and be able to develop their creativity through the works they create.